The effective combination of zirconia superacid and zirconia‑impregnated CaO in biodiesel manufacturing: Utilization of used coconut cooking oil (UCCO) - Sari, Erlin Purwita (International Journal of Energy and Environmental Engineering, 2022)
The present study reports the effective combination of zirconia superacid and zirconia-impregnated CaO in biodiesel manufacturing through the utilization of used coconut cooking oil. The acid catalyst was synthesized by the wet impregnation method combined with H2SO4 0.9 M. This mixture was calcined at 500 °C and yielding the highest catalyst acidity of 3.60 mmol g− 1. The free fatty acid (FFA) levels of UCCO then was reduced through the esterification process by varying the catalyst weight, UCCO-to-methanol mole ratio, calcination temperature, and reaction time. Optimum FFA level was achieved with 5% catalyst weight, 1:15 UCCO/methanol ratio, and 1.5 h reaction time with reduced FFA level to 0.42%. The Zr–CaO catalyst was synthesized using the reflux method through heating at 80 °C for 4 h, achieving the highest catalyst basicity, 27.78 mmol g− 1, at a condition of 1% (w/w) Zr–CaO and calcination temperature of 800 °C. This catalyst was then used in the transesterification reaction to produce biodiesel. Transesterification reaction was carried out by 5% catalyst weight and esterification product to methanol mole ratio of 1:20 for 1.5 h, yielding a conversion value of UCCO into biodiesel of 55.35%.